PAM-1: an antimicrobial peptide with promise against ceftazidime-avibactam resistant Escherichia coli infection - Han, Yijia; Zhang, Yi; Zhang, Xiaodong; Huang, Zeyu; Kong, Jingchun; Wang, Xiuxiu; Chen, Lijiang; Wang, Yue; Cao, Jianming; Zhou, Tieli; Shen, Mo (Frontiers in Microbiology, 2024)
Introduction Antibiotic misuse and overuse have led to the emergence of carbapenem-resistant bacteria. The global spread of resistance to the novel antibiotic combination ceftazidime-avibactam (CZA) is becoming a severe problem. Antimicrobial peptide PAM-1 offers a novel approach for treating infections caused by antibiotic-resistant bacteria. This study explores its antibacterial and anti-biofilm activities and mechanisms against CZA-resistant Escherichia. Coli (E. coli), evaluating its stability and biosafety as well. Methods The broth microdilution method, growth curve analysis, crystal violet staining, scanning electron microscopy, and propidium iodide staining/N-phenyl-1-naphthylamine uptake experiments were performed to explore the antibacterial action and potential mechanism of PAM-1 against CZA-resistant E. coli. The biosafety in diverse environments of PAM-1 was evaluated by red blood cell hemolysis, and cytotoxicity tests. Its stability was further assessed under different temperatures, serum concentrations, and ionic conditions using the broth microdilution method to determine its minimum inhibitory concentration (MIC). Galleria mellonella infection model and RT-qPCR were used to investigate the in vivo antibacterial and anti-inflammatory effects. Results and discussion In vitro antibacterial experiments demonstrated that the MICs of PAM-1 ranged from 2 to 8 μg/mL, with its effectiveness sustained for a duration of 24 h. PAM-1 exhibited significant antibiofilm activities against CZA-resistant E. coli (p < 0.05). Furthermore, Membrane permeability test revealed that PAM-1 may exert its antibacterial effect by disrupting membrane integrity by forming transmembrane pores (p < 0.05). Red blood cell hemolysis and cytotoxicity tests revealed that PAM-1 exerts no adverse effects at experimental concentrations (p < 0.05). Moreover, stability tests revealed its effectiveness in serum and at room temperature. The Galleria mellonella infection model revealed that PAM-1 can significantly improve the survival rate of Galleria mellonella (>50%)for in vivo treatment. Lastly, RT-qPCR revealed that PAM-1 downregulates the expression of inflammatory cytokines (p < 0.05). Overall, our study findings highlight the potential of PAM-1 as a therapeutic agent for CZA-resistant E. coli infections, offering new avenues for research and alternative antimicrobial therapy strategies.